Comparison of Eight Month Coastal Polluted Porcelain and Epoxy Resin Outdoor Insulators - Waluyo Waluyo; Ngapuli I. Sinisuka; Parouli M. Pakpahan; Suwarno Suwarno; Maman A. Djauhari (Institute for Research and Community Services, Institut Teknologi Bandung, 2008)
This study presents the experimental results of eight months naturally coastal polluted outdoor porcelain and epoxy resin insulators. The experiments were leakage current and applied high voltage measurements used a two-channel storage digital oscilloscope, in the hermetically sealed chamber, where temperature, humidity , pressure and applied voltage could be adjusted and measured simultaneously. The leakage current waveforms were analyzed using FFT and the relation to environmental parameters were analyzed using correlation matrix of multivariate statistical tools. It was also conducted SEM and EDAX tests. Base on the correlation coefficient matrix, the humidity contributed to leakage current amplitude and phase angle on the porcelain insulator were very significant, with the correlation coefficient were 0.60 and -0.68 respectively. Whereas, on polluted epoxy resin insulator, the humidity did not influence to leakage current and phase angle considerably. Generally, the surface became rougher than the new one. The most three chemical elements in pollutants were chlorine, silicon and ferrum.